Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2009
DOI: 10.1145/1518701.1518791
|View full text |Cite
|
Sign up to set email alerts
|

Computer usage in daily life

Abstract: In this paper we explore the use of computer at home. This work is based on the automatic recording of application focus data in natural situation from a wide representative panel of 661 households with 1,434 users at home over 19 months. To process these large-scale data, we build a twolevel classification of PC applications describing the whole PC use. At the household level, we worked on computer usage temporality: we observed two strategies of PC usage reflecting a tension between synchronous and asynchron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 20 publications
0
29
0
1
Order By: Relevance
“…The seminal work in that fold is that of Muttka and Livny [12], who studied system idle times, finding that desktop workstations, even in 1990, were idle much of the time. More recent work [4,1] confirms that this remains the case today. Unfortunately, the traces collected from such studies cannot be used to analyze DPM policies since they are too coarse grained, and/or do not capture HID events.…”
Section: Related Workmentioning
confidence: 77%
“…The seminal work in that fold is that of Muttka and Livny [12], who studied system idle times, finding that desktop workstations, even in 1990, were idle much of the time. More recent work [4,1] confirms that this remains the case today. Unfortunately, the traces collected from such studies cannot be used to analyze DPM policies since they are too coarse grained, and/or do not capture HID events.…”
Section: Related Workmentioning
confidence: 77%
“…Consequently, the themes of these had been chosen according to a study of computer usage statistics carried out by Beauvisage (2009), which presented the average distribution of individual weekly computer usage. Notably, the study showed that the four categories identified and selected for the study presented herein, occupy the highest percentages of time spent on computer usage for both households and individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in the domestic use of time have paid some attention to the use of ICTs, but have in many instances (c.f. Beauvisage, 2009) reified a particular conceptualisation of time-asduration, and said less about the affective dimensions of temporality. Both Southerton (2006) and Michelson (2005) therefore suggest a shift in focus with respect to time use, looking towards the qualities of time rather than simply its duration (see also Wacjman, 2008).…”
Section: Home Cultures and Ict Consumption Practicesmentioning
confidence: 99%